Enlightenment in an Age of Destruction Intellectuals, World Disorder, and the Politics of Empire - Britt, Christopher; Fenn, Paul; Subirats, Eduardo (Critical Political Theory and Radical Practice, 2018)
IX, 171 p. 3 illus.